Selective inhibition of histone deacetylase 10: hydrogen bonding to the gatekeeper residue is implicated - Géraldy, Magalie; Morgen, Michael; Ridinger, Johannes; Oehme, Ina; Witt, Olaf (Journal of medicinal chemistry, 2019)
The discovery of isozyme-selective histone deacetylase (HDAC) inhibitors is critical for understanding the biological functions of individual HDACs and for validating HDACs as drug targets. The isozyme HDAC10 contributes to chemotherapy resistance and has recently been described to be a polyamine deacetylase, but no studies toward selective HDAC10 inhibitors have been published. Using two complementary assays, we found Tubastatin A, an HDAC6 inhibitor, to potently bind HDAC10. We synthesized Tubastatin A derivatives and found that a basic amine in the cap group was required for strong HDAC10 binding. HDAC10 inhibitors mimicked knockdown by causing dose-dependent accumulation of acidic vesicles in a neuroblastoma cell line. Furthermore, docking into human HDAC10 homology models indicated that a hydrogen bond between a cap group nitrogen and the gatekeeper residue Glu272 was responsible for potent HDAC10 binding. Taken together, our data provide an optimal platform for the development of HDAC10-selective inhibitors, as exemplified with the Tubastatin A scaffold.
Gesehen am 01.08.2019